Optical Emission Spectroscopic Analysis of Plasma Plume during Pulsed Laser Deposition of PZT. (13th February 2014) - Sasanka Kumar, S.; Reshmi, R.; Joshy, N. V.; Saritha, A. C.; Jayaraj, M. K.
Abstract : Spatial variation in intensity of spectral emission, electron temperature, number density, and the time of flight (TOF) of ions and neutrals at various oxygen ambiances has been investigated on ferroelectric lead zirconium titanate (PZT) plasma using optical emission spectroscopy. Plasma produced by ablating PZT ceramic target using Nd-YAG laser operating at the third harmonics (λ = 355 nm, τ = 10 ns, repetition frequency 10 Hz) was investigated at various oxygen partial pressures and at various distances from the target surface. Here energy density for laser fluence was fixed as 3.13 Jcm −2 and distance from the target and ambient gas pressure were varied. The electron number densityN e and electron temperature of the PZT plasma at the early stage of plume expansion were measured as1.7 × 10 17 Jcm −2 and 13200 K, respectively, and thus verified the existence of local thermodynamic equilibrium (LTE). Time of flight spectra (TOF) of neutral and singly ionized species in plasma were recorded. The result shows that plasma parameters and velocity of species are of same order for various oxygen partial pressures but have a decreasing tendency with distance. The energy of almost all species in the plume become more or less same at 0.1 mbar. These conditions favour the growth of perovskite PZT thin films.